Systematics of the Australian spiny trapdoor spiders of the genus Blakistonia Hogg (Araneae: Idiopidae) - Harrison, Sophie E.; Rix, Michael G.; Harvey, Mark S.; Austin, Andrew D. (Zootaxa, 2018)
A combined molecular and morphological approach was used to revise the Australian spiny trapdoor spiders of the genus Blakistonia Hogg. Where possible, our molecular approach used sequence data from the COI barcoding gene, which were analysed using Bayesian, RAxML and neighbour-joining approaches. These molecular data were combined with morphology to describe and diagnose the genus, to redescribe the type (and only previously valid) species, B. aurea Hogg, 1902, and to diagnose, describe and map 19 new species: B. bassi sp. n., B. bella sp. n., B. birksi sp. n., B. carnarvon sp. n., B. emmottiorum sp. n., B. gemmelli sp. n., B. hortoni sp. n., B. mainae sp. n., B. maryae sp. n., B. newtoni sp. n., B. nullarborensis sp. n., B. olea sp. n., B. parva sp. n., B. pidax sp. n., B. plata sp. n., B. raveni sp. n., B. tariae sp. n., B. tunstilli sp. n., and B. wingellina sp. n. The genus Blakistonia is found to be distributed throughout the Australian arid and semi-arid zones, from the Wheatbelt region of Western Australia to central Queensland and western Victoria.